Optimum planting density for rubber production in Thailand - Jarin Garanad; Somyot Sinthurahat (Papers presented at the IRRDB seminar 5-8 November 1996, Sri Lanka p14)
Rubber inter-row spaces of 8, 7, 6, 5 meters and planting densities of 50, 60, 70, 80, 90, 100, 110 and 120 stands per rai (1 rai = 0.16 ha = 1/6 ha approx) were studied for optimum yield. It was found that the inter-row space had a statistical correlation with rubber girth size during the period up to nine years of age. The number of stands per rai shows a high statistical correlation with rubber girth size both before and after tapping periods. The girth of the lower density stands reached tappable size earlier and gave a higher yield per tree per tapping (g/t/t) than those in the higher density plots. However, the higher density tasks had higher total dry rubber (as sheets) that resulted in a higher accumulated yield than the lower density tasks. From this stydy, it can be recommended that the optimum palnting density for both latex and rubber wood production should be 100 stands per rai when the girth of the rubber trees reaches tappable size within 7 years, according to the regular recommendation of the Rubber Research Institute of Thailand.
Keywords: Girth size; Planting density; Rubber inter-rowspace